A Frequent Problem in Systolic Heart Failure: Fibromyalgia - Kobat, Mehmet Ali; karatas, Ahmet (Cardiology and Cardiovascular Medicine, 2021)
Introduction: heart failure with reduced ejection fraction (HFrEF) is a chronic disease defined as ejection fraction (EF)<40 together with heart failure symptoms, which is progressive and has a high risk of mortality. Fibromyalgia (FM) is defined as chronic pain syndrome, characterized by widespread musculoskeletal system pain, anxiety, orthostatic hypotension, and sleep disorders, with unknown etiology. This study aimed to determine the relationship between FM with heart failure. Material and Method: The study included 131 patients with HFrEF who described widespread body pain who presented at the Cardiology Polyclinic between January 2019 and December 2019 and 91 patients with widespread body pain and not with heart failure. All the patients were evaluated in respect of FM using the 2016 diagnostic criteria. Results: The HFrEF group comprised 65 (49.61%) males and 66 (50.39%) females with a mean age of 67.68 ± 11.41 years and the control group comprised 43 (47.25%) males and 48 (52.75%) females with a mean age of 64.65 ± 12.62 years. The mean EF was 29.22 ± 4.04% in the HFrEF group and 60.10 ± 3.79% in the group control. A diagnosis of FM was made in 27 (20.61%) of the 131 patients with HFrEF and in 5 (5.49%) of the 91 patients control (p<0.05). When a comparison was made of patients with FM using Non-steroid anti-inflammatory drugs (NSAIDs) (6/27, 22.22%) and patients without FM using NSAIDs (8/181, 6.10%), it was determined that patients with FM used NSAIDs at a statistically significantly higher rate (p<0.05). A significant correlation was determined between FM and the severity of depression (p<0.05) and the depression score (p<0.05). Conclusion: The determination of conditions that diminish the quality of life in HFrEF patients can increase their quality of life. While the diag